ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH TERHADAP PEMBERITAAN BANJIR BANDANG SUMATERA UTARA 2025 DI KOMPAS.COM - Rahma Hidayati; Arlin Septia Basana Siagian; Nur Fatimah; Dia Ananda Putri; Poppy Amalia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes the representation of the 2025 North Sumatra flash flood disaster in Kompas.com news coverage using Norman Fairclough's Critical Discourse Analysis (CDA) approach. The data consists of five news articles published between November 26 and December 3, 2025. Analysis was conducted through three levels: textual analysis, discursive practice, and social practice. The findings reveal two dominant patterns in disaster representation. First, naturalization of disaster, evident in the November 26 and December 2, 2025 articles through the use of the word "mystery" and the metaphor "nature's fury," which shifts responsibility away from human actors. Second, politicization of disaster, evident in the November 30 and December 1, 2025 articles through phrases such as "policy disaster" and "policy gap," which frame the flood as a product of systemic government failure. Furthermore, all articles were found to rely on elite sources without providing space for the voices of affected communities, resulting in a top-down and hegemonic discourse. This study confirms that disaster reporting in mainstream media is never neutral, but always shaped by particular ideologies and power relations.